Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis

Organocatalytic route to the synthesis of lactone moiety of compactin and mevinolin - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Tetrahedron Letters, 2010)
An efficient synthesis of lactone moiety of compactin has been achieved. The stereogenic centers were generated by means of iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aminoxylation; Compactin; Lactone; organocatalysis; Proline